THE GROWTH OF THE DOMESTIC MACHINES TOOL INDUSTRY IN THE ECONOMIC CRISIS - O. Demkina; T. Yurchenko (Вестник университета)
The article is about current state and examines the prospects of growth of domestic machine-tool industry. The results of the state program of growth of the machine-tool were investigated. The basic obstacles to the revival and the normal growth of the machine-tool industry in Russia, especially their impact on the developing situation in the world economic system and in the Russian economy. Recommended number of areas in the mainstreaming and effective solution of problems of revival in the Russian machine-tool industry, requiring a change of management in this area.